Pengaruh Senam Lansia terhadap Tingkat Stres di Puskesmas Mekarsari Desa Citeras Kecamatan Rangkasbitung Kabupaten Lebak Tahun 2023 - Wiwit Desi Intarti; Rosana Supriadi; Renince Siregar (Jurnal Kebidanan Harapan Ibu Pekalongan, 2024)
The elderly are those who have reached the age of 60 years and above. As they age, they often face challenges that make it difficult to accept reality, thus affecting their physiological and psychological conditions. Many elderly people experience stress, which then has an impact on the increase in physical and psychological complaints in response to the stress. Elderly gymnastics can be an effective mechanism to improve the stress-related welfare experienced by the elderly. However, the participation of the elderly in this gymnastics activity is still relatively low. The purpose of the study is to find out the “Effect of Elderly Gymnastics on Stress Levels at the Mekarsari Health Center in Citeras Village, Rangkasbitung District, Lebak Regency". Research method Using a quasi-experimental method with a Pre and Post Test design. Types of quantitative research. This sampling technique is with total sampling. The population sample of this study was 48 people while the data analysis was using the T-Test related test. Results of the study Negative Ranks or the difference (negative) between the results of the Elderly Gymnastics Physical Optimization for the Pre Test and Post Test N value is 47 and Mean Rank 25 Sum rank 1175, The above values show a change in the decrease (influence) from the pre test score to the post test score. Based on the results of the statistical test, it is known that Asymp.Sig (2-Tailed) p value 0.00 < 0.05 then (Ha accepted). Conclusion there is an effect of elderly gymnastics on the level of stress at the Mekarsari Health Center, Citeras Village, Rangkasbitung District, Lebak Regency in 2023.